Employing Experiential Learning To Teach Writing For English As A Foreign Language Learners Through A Reflection Project - Adesti Komalasari (International Conference on Education and Language (ICEL), 2013)
Writing is a skill that helps English as Foreign Language (EFL) learners improve their English and also helps them to be exposed more to use English in their day-to-day basis. Unfortunately, writing has been considered as one difficult and boring subject since the learners are merely instructed to write about certain topics or write their daily experiences and past events without clear context and clear directions. Teaching writing has been a challenge since the method of teaching cannot be as various as teaching other competence like speaking or listening. In order to make writing interesting, an English teacher should relate learners’ writing production to their experience. The exposure of experiential learning into some writing production like a weekly reflection or journal would encourage the learners to express more in the composition. This research tries to examine two problem formulations. First, what is the significance of experiential learning in teaching writing? Second, how is experiential learning implemented in the writing production of EFL learners? The objective of the study is to figure out the significance of experiential learning in teaching writing and to find out how experiential learning is implemented in the writing production of EFL learners. Library study would be employed in conducting this research, especially references relate to teaching writing and experiential learning.